2015
DOI: 10.15640/jeds.v3n4a3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ownership Structure and Dividend: An Application in Istanbul Stock Exchange

Abstract: This study defines the ownership structures of 271 real and banking sectors companies registered in the Istanbul Stock Exchange between 2004-2011 years and the impact of ownership structure on dividend was determined by panel data analysis. According to the results of the analysis, it has been observed that the largest shareholder has about 45.37 percent of the shares. Therefore, it has been concluded that companies in the real and banking sector has mostly concentrated ownership structure. Ownership structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(47 reference statements)
2
7
1
5
Order By: Relevance
“…The results also indicated that the ownership composition affected dividend, where a negative relationship was observed for shareholding by individuals and a positive relationship observed for shareholding by insurance companies. Sakinc & Gungor (2015) investigated the impact of ownership structure on dividend for 271 real and banking firms listed on Istanbul Stock Exchange between 2004-2011. The results indicated that the cash dividend was associated positively with ownership concentration and negatively with foreign ownership.…”
Section: Ownership Concentrationmentioning
confidence: 99%
“…The results also indicated that the ownership composition affected dividend, where a negative relationship was observed for shareholding by individuals and a positive relationship observed for shareholding by insurance companies. Sakinc & Gungor (2015) investigated the impact of ownership structure on dividend for 271 real and banking firms listed on Istanbul Stock Exchange between 2004-2011. The results indicated that the cash dividend was associated positively with ownership concentration and negatively with foreign ownership.…”
Section: Ownership Concentrationmentioning
confidence: 99%
“…Tobit modelinden (Model 1) elde edilen tahmin sonuçlarına göre, sahiplik yoğunlaşmasını temsilen kullanılan en büyük üç ortağın payı değişkenine ait katsayı pozitif ve istatistiksel olarak anlamlıdır. Bu sonuç, temettü verimi ile en büyük üç ortağın payı arasında pozitif yönlü bir ilişkinin olduğunu göstermektedir ve Stacescu (2012), Thanatawee (2013), Djebali ve Belanes (2015), Sakinc ve Gungor (2015), Ersoy ve Çetenak (2015) ve Aydin'ın (2015) çalışmasında elde edilen bulgularla uyumludur. Ayrıca elde edilen bu sonucun, Rozeff (1982), Easterbrook (1984) ve Jensen'in (1986) yaklaşımıyla tutarlı olduğu, sinyal yaklaşımı ile Shleifer ve Vishny'nin (1997) yaklaşımıyla çeliştiği söylenebilir.…”
Section: Ampirik Bulgularunclassified
“…Dolayısıyla şirketlerin halka açık-lık oranı arttıkça, kar payı dağıtım oranı azalmaktadır. Sakinc ve Gungor (2015), Wei, Zhang ve Xiao (2003) ve Rezaloie, Zariean ve Bjarkenari (2013) de çalışmalarında benzer sonuçlar elde etmiştir. Şirketlerin halka açıklık oranının artması durumunda sermayenin daha fazla tabana yayılacağı ve şirketlerin daha dağınık bir sahiplik yapısına sahip olacağı, dolayısıyla şirketle-rin sahiplik yapısındaki yoğunlaşmanın azalacağı kabul edilmektedir.…”
Section: Ampirik Bulgularunclassified
“…This fact may be due to the fact that several large shareholders find it easier to agree on the amount of dividends. Additionally, the higher the cumulative share of the largest shareholders in a company, the greater the amount of profit allocated for the payment of dividends [6]. In state-owned companies, high dividends are likely for two reasons: managers will strive to demonstrate the company's successful activity to the country's population, the second reason is a reduction in cash flow in the hands of the managerial apparatus, which will reduce potential investment risk, and also entail an increase in budget revenues due to dividend payments [7].…”
Section: Introductionmentioning
confidence: 99%